From the West to the East: an evidence-based educational reform for modern medical students in traditional Chinese medicine learning - Liu, Zhenrui; Ren, Zhixuan; Fang, Linhan; Liao, Yuxuan; Ren, Dan; Yu, Yao; Qin, Yixuan; Wu, Jianzhen; Rong, Pengfei (Frontiers in Medicine, 2023)
Introduction Generally, Traditional Chinese Medicine (TCM) courses are now given to modern medicine students without proper course scheduling, resulting in poor teaching results. Methods To analyze the main factors affecting TCM learning, we surveyed the medical students and TCM teachers from Xiangya School of Medicine of Central South University via online questionnaires. The questionnaire comprised two parts, the students' part included the basic information, the subjective cognition in TCM, the attitude toward TCM course arrangements, and the attitude toward curriculum content and the design of TCM. The teachers' part included the basic information, the attitudes and opinions on TCM course arrangements, and suggestions and views on TCM teaching reform. The related data were collected from 187 medical students divided into two groups, namely, clinical medical students and non-clinical medical students. Results We found a more positive attitude toward TCM [including “Scientific nature of TCM” (P = 0.03) and “Necessity for modern medicine students to learn TCM” (P = 0.037)] in clinical medical students compared with non-clinical medical students, clinical and non-clinical medical students tended to find TCM courses difficult, and the students prefer clinical training to be better than theoretical teaching, while the teachers believe that lecture-based education should have a more significant proportion. Discussion Hence, to optimize the current TCM teaching, we conducted education reform, including differentiated teaching, hybrid teaching, and selective teaching.